SARATHI BANTEN DI BALI ANTARA PROFESI DAN YADNYA DALAM PERSPEKTIF PERSAINGAN PASAR BEBAS - Adhikang, Lilawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Of the three basic frameworks of Hinduism which consist of Tattwa, Susila and Upacara, the elements of the ceremony that look very dominant compared to the other two. Ceremonial facilities usually called banten consist of many components, knick-knacks vary with various types of variations. Nowadays, preparing ceremonial facilities is no longer possible to make itself, the practicality paradigm, fast because it is pursued by a limited time so buying facilities is a fast, appropriate and safe choice. The demand for fast and instant modern society opens opportunities for service providers and ceremonial products. The emergence of the banter artisans or Sarathi who are ready to provide all the ceremonial necessities quickly. This collaboration on the basis of mutual need raises new social capital in the community. Sarathi is a fast-paced social capital that will be contested by the perpetrators to become a new industry. There is demand followed by the provision of placing Sarathi as the seller of the providers of cash facilities. Sarathi enters the market for aid facilities like the market will be competitive. Free competition in the digital era is one of them. Sarathi Banten will be a special profession sought by modern society. This study will answer the role of Sarathi in the Hindu view, the role of Sarathi in being part of traditional free market competitionand the digital era and to provide a view of the role of government and publicity institutions to Sarathi so that they are able to play a role in tattwa but survive in the market.